KAJIAN ETNOSAINS BUDAYA KAMPUNG NAGA SEBAGAI SUMBER PEMBELAJARAN IPA DI SEKOLAH DASAR - Azzahra, Umaya; Hamdu, Ghullam; Putri, Agnestasia Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Along with technological advances and globalization, Indonesia a country with the world’s greatest cultural diversity faces serious challenges in preserving its cultural heritage. One strategic effort to address this is the integration of local wisdom into education. This research examines how the traditional knowledge of the Kampung Naga community, as reflected in their cultural practices, can be transformed into scientific knowledge and utilized as a learning resource for elementary school science. A descriptive qualitative method was employed, with data collected through interviews, observations, and literature studies. The data were analyzed using the Miles-Huberman model, which involves data reduction, data presentation, conclusion drawing, and verification. The results indicate that several cultural practices of the Kampung Naga community such as the Hajat Sasih Ceremony, the Sengkedan System, and Cai Seke can be linked to scientific concepts. These practices are applicable to elementary science education, particularly in topics such as natural resource conservation, energy and its transformations, the water cycle, adaptation of living organisms, and environmental changes.